Canto em marcha: música folk e direitos civis nos Estados Unidos (1945-1960) - Arantes, Mariana Oliveira [UNESP] (2014)
The present research analyzes the relations between the music and the politics in the United States, specifically the composers and interpreters actions in the fights for national minorities civil rights. Our temporal snippet covers the post-Second World War period, between 1945 and 1960, in which occurs the emergency of the country as the hegemonic nation among the Occidental countries, followed by the placement of a democratic discourse, that had its limit in an unequal and segregated society. In this way, the civil rights fights, before set boundaries in legal actions, as the judicial proceedings in Courts, were oriented to expansive and public spaces, as the streets and squares through the country, and they had the support from distinctive social groups, including musicians related to the folk repertoire. Due the absence of American folk music bibliography in Brazil, our first chapter deals with the relations between folk music and the American historical context throughout the twentieth century, showing how this repertoire has become a controversial subject of national cultural study, which were the genres settled as folk music and their diffusion process from rural areas to cities, as well as its insertion in the music market. In our second chapter, we deal with the production of the mainly reference in the folk recording activity in the country, the Folkways Records, listing the persons inserted in the disc producing process, as well the discourses propagated through these products. In this sense, we believe to be vital to comprehend its historical period and its role in the national music market. Adopting as documentation to this research two musical magazines published in the United States, People's Song and Sing Out!, make necessary to analyze the social groups involving in the creation and development of the magazines, in other words, to analyze their textual and paratextual dimensions - this is the objective of the third...